Community Involvement in Urban Water Management: The N Park Resort Condominium Rainfall Harvesting and Water Saving Project in Penang, Malaysia - Ngai Weng Chan; Jabil Mapjabil; Narimah Samat; Mou Leong Tan; Aminuddin Ab Ghani; Fei Zhang (Populasi, 2021)
Community engagement and involvement is vital for the success of urban water management. However, poor public engagement, cheap water tariffs, apathetic attitude and lack of public interest are identified as the main reasons for high water wastage in Penang State, Malaysia. The N Park Resort Condominium rainfall harvesting and water saving project in Penang, Malaysia is a prime example of successful urban water management involving government, private sector, non-governmental organisations (NGOs) and local communities. The N-Park condominium consisting of 965 units is the first condominium in the country to initiate a community water- saving project. Started in August 2009 and completed in December 2010, the project is jointly implemented by the Drainage and Irrigation Department (DID) Malaysia (Government), Water Watch Penang (WWP) (NGO), N-Park Management Corporation (NPMC)(Community) and the Penang Water Supply Corporation (PWSC). The methodology involved installation of a rainwater harvesting system, installation of water-saving devices and a water-saving campaign. Results of the project showed that the rainwater harvesting system was most successful as the rainwater harvested was used for gardening, washing common areas and toilets, flushing toilets, and washing vehicles. The installation of water-saving devices was also successful as it resulted in substantial water savings. Results showed reduced total water usage from 8 to 25 % between September 2009 to March 2010. The greatest reduction by 50 % was between May and July 2011, followed by 47.5 % in January 2011. During the time of the project, the amount of water saved was equivalent to RM1,3971 in monetary savings per month. Over a year, this is translated to a savings of 16,818 m3 of water or the equivalent of RM 16,782. More recently, between February 2020 and April 2021, the average water saved was 5852 m3 per month or averaging 48.77 % per month, equivalent to about RM34,255. Results also showed enhanced water awareness and better relationships between neighbours. Overall, this project proved that collaboration between government-private sector-NGOs is workable, and the project can be replicated nation-wide in apartments, hotels, factories, universities, and schools.